PENGARUH CAR, INFLASI, NILAI TUKAR TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH - Fretty Welta; Lemiyana Lemiyana (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2017)
This research using causal assosiative method. The data using time series and cross section period 2011 – 2015 with SPSS application. The population are Bank Umum Syariah (BUS) in Indonesia which is registered in Bank Indonesia directory period 2011 – 2015 that is 11 Bank Syariah. The result showed that Capital Adequacy Ratio (CAR) has no negative influence to ROA. Inflation and exchange rate variabeles has no influence significantly to ROA.